Branch Duct Intraductal Papillary Mucinous Neoplasms: Recommendations for Follow-Up and Surgery. (March 2020) - Caravati, A.; Andrianello, S.; Pollini, T.; Biancotto, M.; Balduzzi, A.; Malleo, G.; Salvia, R.; Marchegiani, G.
Background and Aims: Pancreatic cysts are increasingly diagnosed, mainly during abdominal imaging performed for other reasons. Between pancreatic cystic neoplasm, intraductal papillary mucinous neoplasms are the most common pre-malignant entities. Intraductal papillary mucinous neoplasms involving side branches overall harbor a low risk of malignancy, and in the recent past, a progressively more conservative approach has been consolidated. Purpose of this report is to summarize the evidence supporting the current practice for the management of branch duct intraductal papillary mucinous neoplasm and to offer a useful practical guide from first observation to post-operative follow-up. Materials and Methods: Review of the most important scientific literature on intraductal papillary mucinous neoplasms was made. In this review article, we also report the experience of a high volume center in managing Pancreatic cystic neoplasms. Results: The correct management during surveillance still is a matter of debate, since many guidelines have been published suggesting different clinical approaches. Recently, follow-up discontinuation has also been proposed in selected cases. Conclusion: Despite significant improvements made by the increase of evidence, selecting surgical candidates because of an increased risk of malignant progression remains an unsolved issue and a hot topic for pancreatologists.